TECHNOLOGY-DRIVEN TRENDS IN HOSPITALITY: THE RISE OF SMART HOTELS IN THE DIGITAL ERA - Singh, Surendra; Sharma, Monu; Bangad, Peeyush Raj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the integration of smart technologies in the hospitality sector, focusing on customer perceptions, adoption rates, and operational outcomes of smart hotels. Using a mixed-method approach and data from 150 respondents, the research evaluates critical factors influencing the acceptance of smart hotel technologies, including demographic variables, perceived benefits, and barriers. Advanced statistical techniques such as ANOVA, Chi-Square tests, and correlation analysis were applied to test hypotheses and derive meaningful insights. The results reveal that customer satisfaction and operational efficiencies significantly influence the adoption of smart hotel technologies, while challenges like data privacy concerns and high costs impede widespread implementation. The study highlights the role of automation, IoT-enabled services, and AI in enhancing customer experiences and streamlining operations. The findings underscore the need for tailored strategies to address diverse customer preferences and demographic variations, as well as robust solutions to mitigate privacy and cost concerns. This research contributes to both academic literature and practical applications by offering actionable recommendations for hotel operators aiming to maximize the benefits of smart technologies while addressing potential barriers.